2006
DOI: 10.1101/gad.377506
|View full text |Cite
|
Sign up to set email alerts
|

X-chromosome-wide profiling of MSL-1 distribution and dosage compensation inDrosophila

Abstract: In Drosophila, dosage compensation is achieved by a twofold up-regulation of the male X-linked genes and requires the association of the male-specific lethal complex (MSL) on the X chromosome. How the MSL complex is targeted to X-linked genes and whether its recruitment at a local level is necessary and sufficient to ensure dosage compensation remain poorly understood. Here we report the MSL-1-binding profile along the male X chromosome in embryos and male salivary glands isolated from third instar larvae usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 52 publications
5
107
0
Order By: Relevance
“…However, the equal expression of X-linked genes between females and males is achieved through dosage compensation mechanisms. 36) Genetics studies have implicated three Msl genes, Msl1, Msl2, and Msl3 in dosage compensation; 37) these genes were also identified in the sexual glands of H. schlegelii. Realtime PCR analysis revealed that the expression levels of the three Msl genes were significantly higher in the sperm than in the ovary.…”
Section: Expression and Regulation Of Genes Related To Sex Determinatmentioning
confidence: 99%
“…However, the equal expression of X-linked genes between females and males is achieved through dosage compensation mechanisms. 36) Genetics studies have implicated three Msl genes, Msl1, Msl2, and Msl3 in dosage compensation; 37) these genes were also identified in the sexual glands of H. schlegelii. Realtime PCR analysis revealed that the expression levels of the three Msl genes were significantly higher in the sperm than in the ovary.…”
Section: Expression and Regulation Of Genes Related To Sex Determinatmentioning
confidence: 99%
“…In flies, dosage compensation is accomplished by the male-specific lethal (MSL) complex, composed of proteins and RNA. The MSL complex binds within the body of X-linked genes and alters chromatin to enhance transcription (Alekseyenko et al 2006;Gilfillan et al 2006;Legube et al 2006). The protein-coding components of the MSL complex were identified by the male-specific lethality of mutations in these genes.…”
mentioning
confidence: 99%
“…The sequences of the primers are available on request. Chromatin 537 immunoprecipitation was performed according to the protocol of Legube et al (2006). Chromatin 538 was prepared either from 10 7 S2 cells or 100 pairs of L3 salivary glands.…”
Section: Chip 535mentioning
confidence: 99%